A modified resistance to compression (RtC) test for evaluation of natural fiber softness. Issue 11 (June 2022) - Yu, Hao; Hurren, Christopher; Liu, Xin; Gordon, Stuart; Wang, Xungai
Comfort is a key feature of any clothing that relates significantly to softness of the fiber, yarn and fabric from which is it constructed. A known softness assessment method for fibers is the resistance to compression test. This traditional test only provides a single force value for the resistance of a loose fiber sample using a fixed mass under compression. In this research, a modified resistance to compression test was introduced to show the effects of repeated compression, providing more information about the softness and resilience of selected fibers. Three different natural fiber types, including wool, cotton and alpaca were compared using this new approach. The results showed compression profiles were quite different for different fiber types as well as for the same fibers with different diameters. While the diameters of the wool and alpaca samples were similar (18.5 μm), the modified resistance to compression values were significantly higher for wool (with a peak value at 9.5 kPa compared to 2.1 kPa for alpaca). Cotton was different from wool and alpaca but showed a similar modified resistance to compression value (10.4 kPa) to wool. During cycles of compression, modified resistance to compression peak values decreased slightly and then tended to be constant. Even though the structures of wool, cotton and alpaca were quite different, there was no significant difference in the magnitude of decline in modified resistance to compression peak values. This means that the modified resistance to compression test is able to provide additional information on the resilience characteristics of different natural fibers, and can reveal the resistance behavior of fiber samples during cyclic compression.